Playful activities that create a dynamic environment which fosters english listening and speaking skills at La Colonia Elementary School with students from 6 to 12 years old, 2017 - Santamaría Montes, María Soledad (UDELAS, 2017)
El proyecto esta enfocado en niños y niñas a entender y reforzar el inglés de una manera divertida, y beneficiará a los alumnos de la escuela primaria La Colonia.